The Effect of Blood Loss on the Hemodynamics of Pediatric Patients Undergoing Simultaneous Bilateral Cochlear Implantation - BATMAN, ABDULLAH ÇAĞLAR (GALENOS YAYINCILIK, 2020)
Objective: Our objectives were to find the mean blood loss volume and the mean hemoglobin decrease in patients undergoing simultaneous bilateral cochlear implant surgery, to determine whether they had clinical effects, and to calculate a minimum weight for pediatric patients that is independent of any age criteria. Methods: A retrospective chart review of the pre- and post-operative hemoglobin concentrations and mean blood loss volumes were calculated for children between 12-24 months of age who underwent cochlear implant surgery. Results: A postoperative decline in hemoglobin concentration was found in 67 cases (92%), with a mean difference between the pre- and post-operative values measuring 1.9 g/dL. Preoperative hemoglobin concentrations decreased from 13.4 g/dL to 11.5 g/dL. Mean blood loss volume was 82.3 +/- 12 cc. Conclusion: Although simultaneous bilateral cochlear implant surgery is reimbursed by the state for those who are greater than one year of age and who meet the appropriate audiological criteria, our findings suggest that these patients should weigh >= 10 kg to prevent hemodynamic instability due to blood loss during surgery.
Keywords: Child; cochlear implantation; hemodynamics; hemoglobin; ideal body weight; TRANSFUSION; CHILDREN